Factors affecting conception rates following artificial insemination or embryo transfer in lactating holstein cows - Demetrio, D. G. B.; Santos, R. M.; Demetrio, C. G. B.; Vasconcelos, José Luiz Moraes [UNESP] (Amer Dairy Science Assoc-adsa, 2007)
The objective of this study was to evaluate the factors that may affect conception rates (CR) following artificial insemination (AI) or embryo transfer (ET) in lactating Holstein cows. Estrous cycling cows producing 33.1 +/- 7.2 kg of milk/d received PGF(2 alpha) injections and were assigned randomly to 1 of 2 groups (AI or ET). Cows detected in estrus (n = 387) between 48 and 96 h after the PGF2a injection received AI (n = 227) 12 h after detection of estrus or ET (n = 160) 6 to 8 d later (1 fresh embryo, grade 1 or 2, produced from nonlactating cows). Pregnancy was diagnosed at 28 and 42 d after estrus, and embryonic loss occurred when a cow was pregnant on d 28 but not pregnant on d 42. Ovulation, conception, and embryonic loss were analyzed by a logistic model to evaluate the effects of covariates [days in milk (DIM), milk yield, body temperature (BT) at d 7 and 14 post-AI, and serum concentration of progesterone (P4) at d 7 and 14 post-AI] on the probability of success. The first analysis included all cows that were detected in estrus. The CR of AI and ET were different on d 28 (AI, 32.6% vs. ET, 49.4%) and 42 (AI, 29.1% vs. ET, 38.8%) and were negatively influenced by high BT (d 7) and DIM. The second analysis included only cows with a corpus luteum on d 7. Ovulation rate was 84.8% and was only negatively affected by DIM. Conception rates of AI and ET were different on d 28 (AI, 37.9% vs. ET, 59.4%) and 42 (AI, 33.8% vs. ET, 46.6%) and were negatively influenced by high BT (d 7). The third analysis included only ovulating cows that were 7 d postestrus. Conception rates of AI and ET were different on d 28 (AI, 37.5% vs. ET, 63.2%) and 42 (AI, 31.7% vs. ET, 51.7%) and were negatively influenced by high BT (d 7). There was a positive effect of serum concentration of P4 and a negative effect of milk production on the probability of conception for the AI group but not for the ET group. The fourth analysis was embryonic loss (AI, 10.8% vs. ET, 21.5%). The transfer of fresh embryos is an important tool to increase the probability of conception of lactating Holstein cows because it can bypass the negative effects of milk production and low P4 on the early embryo. The superiority of ET vs. AI is more evident in high-producing cows. High BT measured on d 7 had a negative effect on CR and embryonic retention.
Keywords: embryo transfer; artificial insemination; conception rate; dairy cow